Factors Influencing Rural Dwellers Participation in Millennium Village Project (MVP) in Pampaida, Kaduna State, Nigeria - M, Barnabas Tena; G, Akpoko Joseph; O, Akinola Michael; A, Nandi James (Asian Journal of Agriculture and Rural Development, 2014)
This study examines the factors influencing rural dwellers participation in Millennium Village Project (MVP) in Pampaida of Kaduna State, Nigeria. Specifically the socio-economic characteristic of the beneficiaries of the project were identified; and factors influencing rural dwellers participation in the project examined. Data collection process was through the use of structured questionnaire. The study used 120 questionnaires administered to randomly selected respondents in 28 settlements divided into 4 clusters of 7 settlements each. Descriptive statistics and multiple regressions were used to analyze the data. The findings show that most of the respondents were experienced young small scale male adult farmers with little formal education (42%) and massive contact with extension agents. Furthermore, age, income, educational attainment, farm size and extension contact were the reasons why the respondents participated in the MVP. Therefore, the following recommendations were made: more adult education centers should be established in the area, as well as more facilitators employed to increase the educational level of the programme participants; soft loans should be granted to the farmers to offset the bureaucratic procedures for credit facilities.